Photoacoustic spectroscopy of aromatic amino acids in proteins - Bugs, Milton Roque; Bortoleto-Bugs, Raquel Kely; Cornelio, Marinonio Lopes [UNESP] (Springer, 2008)
This paper concerns the use of photoacoustic spectroscopy (PAS) to study the presence of aromatic amino acid in proteins. We examined the aromatic amino acids in six proteins with well-known structures using absorption spectra of near ultraviolet PAS over the wavelength range 240-320 nm. The fundamental understanding of the physical and chemical properties that govern the absorption of light and a subsequent release of heat to generate a transient pressure wave was used to test the concept of monitoring aromatic amino acids with this method. Second derivative spectroscopy in the ultraviolet region of proteins was also used to study the regions surrounding the aromatics and the percentage area in each band was related in order to determine the contribution in function of the respective molar extinction coefficients for each residue. Further investigation was conducted into the interaction between sodium dodecyl sulphate (SDS) and bothropstoxin-I (BthTx-I), with the purpose of identifying the aromatics that participate in the interaction. The clear changes in the second derivative and curve-fitting procedures suggest that initial SDS binding to the tryptophan located in the dimer interface and above 10 SDS an increased intensity between 260 and 320 nm, demonstrating that the more widespread tyrosine and phenylalanine residues contribute to the SDS/BthTx-I interactions. These results demonstrate the potential of near UV-PAS for the investigation of membrane proteins/detergent complexes in which light scattering is significant.
Keywords: Photoacoustic spectroscopy; aromatic amino acids; curve-fitting; bothropstoxin-I; SDS